You only call when you're in trouble : [large type] a novel - McCauley, Stephen (Thorndike Press large print top shelf., 2024)
"After a lifetime of taking care of his sister and niece, Tom is ready to put himself first. An architect specializing in tiny houses, he finally has an opportunity to build his masterpiece. Assuming, that is, he can keep the demands of his family at bay. Naturally, that's when his phone rings. His niece, Cecily, is embroiled in a Title IX investigation at the college where she teaches that threatens her career and relationship. And after decades of lying, his sister wants to tell Cecily the real identity of her father. Tom does what he's always done--answers the call. Thus begins a journey that will change everyone's life"--